An uncommon twist to a common event – Isolated enteric splenic infarcts and abscesses - Dutta, Meghna; Chatterjee, Suddhasatwya (Eastern Journal of Medical Sciences, 2020)
Isolated splenic abscess associated with enteric fever is uncommon with very few reported cases in the literature. Till recently, the condition was more frequently diagnosed at necropsy. Splenic abscess is mostly encountered solitarily rather than being multiple and can be fatal if untreated. Various conditions interfere with the prognosis of splenic abscess such as underlying diseases, abscess number and size, organism spectra, and general conditions. This unusual and potentially life-threatening disease is a diagnostic challenge due to its non-specific clinical picture. High index of suspicion and liberal use of imaging studies are essential for timely diagnosis. We report a case of enteric splenic abscess in an immunocompetent patient without any comorbidities, which was diagnosed by blood tests, ultrasonography, and computed tomography scan and successfully managed conservatively with antibiotics.